Erratum: Author Correction: A chip-integrated coherent photonic-phononic memory (Nature communications (2017) 8 1 (574)) - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Nature Communications, 2018)
The original version of this Article omitted the Acknowledgements section:"This work was sponsored by the Australian Research Council (ARC) Laureate Fellowship (FL120100029) and the Centre of Excellence program (CUDOS CE110001010). We acknowledge the support of the ANFF ACT."This has now been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2021-06-29